Relationship between high fructose price and mexican bee honey price - Luis-Rojas, Samuel; García-Sánchez, Roberto Carlos; García-Mata, Roberto; Arana- Coronado, Oscar Antonio; Ramírez-Valverde, Benito (Ecosistemas y Recursos Agropecuarios, 2023)
Beekeeping in Mexico as a generator of foreign exchange is among the top three places in the livestock sector, its main product is honey. The objective of this study was to evaluate the direction of temporary or permanent causality of the average wholesale price of high fructose corn syrup in Mexico (PPMJF) in the average price paid to the producer of honey in Mexico (PPPML). The data correspond to the period 1994 to 2021 and were processed using the vector autoregressive (VAR) methodology. The model parameters were estimated using the ordinary least squares (OLS) method in EViews®. The estimated model indicates that the PPPML series responds to a disturbance shock of the PPMJF variable in a temporary positive manner from the second year. The Wald test indicated that the PPMJF series does not cause the PPPML variable in the Granger sense, however, PPPML does cause the PPMJF in the Granger sense. The VAR model showed that the PPMJF has a positive impact on the PPPML temporarily and does not exert significant effects as an external factor on the price of honey paid to the producer in Mexico.